The EU needs a social investment pact - Vandenbroucke, Frank; Hemerijck, Anton; Palier, Bruno (Brussels, 2011)
"In this Opinion Paper, three of the leading EU social scientists argue that important long-term EU social and economic policy goals must not fall victim to short-term policy considerations triggered by the banking crisis that hit the global economy in 2008. They encapsulate these long-term goals in the notion of a “social investment imperative” and warn for the dangerous mix of welfare chauvinism and fiscal austerity nationalism dividing Europe. "